The Hue of Concepts. (December 2013) - Albertazzi, Liliana; Canal, Luisa; Malfatti, Michela; Micciolo, Rocco
The study shows a systematic naturally biased association between percepts and concepts. Specifically, it shows that a series of terms pertaining to an abstract semantic field (related to the frame of ethics in social behaviour) has a nonrandom, highly significant, association with colours (hues). This is the first time that consistent associations between abstract terms and colours have been reported in the general population. The main hypothesis, ie that there appear to be 'hues of concepts', was borne out by the results: The abstract terms considered were coloured with blue/green (ie cool) colours as well as their synonyms, while their antonyms were coloured with red/yellow (ie warm) colours. The association provides information about the nature of abstract concepts and their relationship with perception. It also sheds light on the interrelations among words in semantic domains that, to date, have been studied from only a computational viewpoint.